OTORITAS AHLI WARIS DENGAN MASALAH KEJIWAAN TERHADAP HARTA WARISAN DALAM PERSPEKTIF HUKUM ISLAM - Aqqhila Felia Putri; Kristianti, Dewi Sukma (Faculty of Law, Parahyangan Catholic University, 2024)
This study examines the obligations and authority of heirs with psychiatric conditions in managing their inheritance from the perspective of Islamic inheritance law. It addresses the issue of heirs with psychiatric problems, who are often assumed capable of fulfilling their obligations and managing their inheritance. Such heirs are frequently equated with children or individuals with severe mental illness, who typically rely on family assistance. The study explores two main legal issues: (1) the applicability of heirs' obligations under the Compilation of Islamic Laws (KHI) to those with psychiatric conditions, and (2) their authority to manage their inherited property under Islamic inheritance principles. Using socio-legal research methods—including statutory, conceptual, and comparative approaches—the study finds that heirs with psychiatric conditions can bear obligations under KHI as they are considered ahliyah al-ada (legally capable). Their obligations primarily pertain to the transfer of inheritance, which they can perform. Regarding the management of their inheritance, such authority is granted if they can make rational decisions, particularly in cases of episodic or relapsing psychiatric disorders with non-continuous symptoms. However, in cases of permanent, continuous, and incurable mental disorders, these heirs are placed under the oversight of a supported decision-making system.